Development of Islamic Religious Education Teaching Materials Based on Problem Based Learning to Improve Cognitive Learning Outcomes of Grade VIII Students at MTs Miftahul Falah - Irfan Ahmad Zain; Wendi Saepul Mikdar; Roby Salim (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Student learning outcomes play a crucial role in the educational process and are also one of the goals of the learning process in schools. Therefore, educators must understand and master various learning methods and models. This is expected to help students understand the learning material and improve student learning outcomes. The purpose of this study was to determine the effect of implementing a problem-based learning model on improving the cognitive learning outcomes of eighth grade students at MTs Miftahul Falah, Bandung City. This study employed a quantitative approach and a quasi-experimental method. The data sources used were primary and secondary data, with the following data collection tools: observation, tests, and documentation studies. The results showed a significant effect of the application of the problem-based learning model on students' cognitive learning outcomes, with a 12% increase in learning outcomes.